Comparison of three interval arithmetic‐based algorithms for antenna array pattern upper bound estimation. Issue 14 (1st July 2019) - He, Guolong; Gao, Xin; Zhou, Hui; Zhu, Hongquan
Abstract : This Letter reveals the underlying relations of three state‐of‐the‐art interval arithmetic (IA)‐based algorithms for antenna array pattern upper bound estimation with excitation amplitude errors. Theoretical analysis proves that the matrix IA algorithm has better performance than both the rIA and circular IA algorithms. Mathematical derivations are presented in detail, and representative numerical examples are given for validating this conclusion.